1994
DOI: 10.1038/ng0794-433
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of imprinting of IGF2 is linked to reduced expression and abnormal methylation of H19 in Wilms' tumour

Abstract: The insulin-like growth factor-II (IGF2) and H19 genes are imprinted in mouse and human, with expression of the paternal IGF2 and maternal H19 alleles. IGF2 undergoes loss of imprinting (LOI) in most Wilms' tumours (WT). We now show that: (i) LOI of IGF2 is associated with a 80-fold down regulation of H19 expression; (ii) these changes are associated with alterations in parental-origin-specific, tissue-independent sites of DNA methylation in the H19 promoter; and (iii) loss of heterozygosity is also associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
285
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(299 citation statements)
references
References 49 publications
10
285
4
Order By: Relevance
“…The present data also show that allelic expression patterns of H19 and IGF2 in TGCTs are different from other type of neoplasms (Moulton et al, 1994;Steenman et al, 1994;Taniguchi et al, 1995;Cui et al, 2001;Nakagawa et al, 2001;Ulaner et al, 2003): null expression, monoallelic expression and biallelic expression of both H19 and IGF2 were observed in TGCTs with consistent unmethylated DNA profiles of H19 (Table 1). Biallelic expression of both IGF2 and H19 has been reported in TGCTs of adolescents (van Gurp et al, 1994;Nonomura et al, 1997;Verkerk et al, 1997) and pediatrics (Ross et al, 1999).…”
Section: T Kawakami Et Alsupporting
confidence: 65%
See 3 more Smart Citations
“…The present data also show that allelic expression patterns of H19 and IGF2 in TGCTs are different from other type of neoplasms (Moulton et al, 1994;Steenman et al, 1994;Taniguchi et al, 1995;Cui et al, 2001;Nakagawa et al, 2001;Ulaner et al, 2003): null expression, monoallelic expression and biallelic expression of both H19 and IGF2 were observed in TGCTs with consistent unmethylated DNA profiles of H19 (Table 1). Biallelic expression of both IGF2 and H19 has been reported in TGCTs of adolescents (van Gurp et al, 1994;Nonomura et al, 1997;Verkerk et al, 1997) and pediatrics (Ross et al, 1999).…”
Section: T Kawakami Et Alsupporting
confidence: 65%
“…The common expression patterns in TGCTs were biallelic expression of H19 and null expression of IGF2 in the present study (Table 1). The patterns of H19/IGF2 expression were in contrast to those in Wilms' tumors (Ogawa et al, 1993;Rainier et al, 1993;Moulton et al, 1994;Steenman et al, 1994;Taniguchi et al, 1995;Feinberg and Tycko, 2004).…”
Section: T Kawakami Et Almentioning
confidence: 69%
See 2 more Smart Citations
“…Although de novo methylation and silencing of H19 in Wilms' tumours was first reported some years ago (Steenman et al, 1994;Taniguchi et al, 1995), epigenetic changes have not been investigated in great detail in Wilms' tumour. Recently, we reported frequent CASP8 (43%) and RASSF1A (56%) promoter methylation in Wilms' tumours and the present study has demonstrated that SLIT2 methylation represents a further frequent epigenetic change in Wilms' tumours.…”
Section: Discussionmentioning
confidence: 99%